Improved mechanical properties of NbC-M2 high speed steel-based cemented carbide by addition of multi-walled carbon nanotubes. (December 2020) - Esmaeilzadeh, Reza; Zamani, Cyrus; Reinhardt, Hendrik; Dasbach, Michael; Hampp, Norbert; Hadian, Amir; Hadian, Ali Mohammad
Abstract: Multi-walled Carbon Nanotubes (MWCNTs) are added to NbC-12 vol% M2 high-speed steel to investigate the effect on microstructural and mechanical properties. Powder mixtures containing small amounts of MWCNTs (0, 0.1, 0.3 and 0.9 wt%) were prepared and shaped into pellets using cold compaction. The green samples were sintered under high vacuum condition for 1 h at 1360 °C. In order to study the microstructure and phase evolution of the sintered cemented carbide, field-emission scanning electron microscopy (FESEM) equipped with energy-dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD) analysis were used. Density was measured using Archimedes method and Vickers hardness was performed to characterize the mechanical properties including hardness and fracture resistance. Results show that addition of MWCNTs from 0 to 0.3 wt% significantly increases the hardness from 1101 ± 18 to 1470 ± 22 HV. However, higher MWCNTs content causes reduction in hardness value down to 997 ± 26 for 0.9 wt%. FESEM images and density measurement reveal better densification of the cemented carbide by adding MWCNTs up to 0.3 wt%. Further microstructural investigations on indented samples showed remarkable bridging mechanism activated by the presence of nanotubes in the sample containing 0.3 wt%. Despite the toughening effects of MWCNTs, the fracture resistance slightly improved and reached the maximum value of 3.55 ± 0.08 MPa.m 0.5 for NbC-M2–0.3 wt% MWCNTs. According to XRD phase analysis, no compositional changes were detected in samples containing MWCNTs. Graphical abstract: Unlabelled Image Highlights: Pore elimination of NbC-M2 HSS cemented carbide by addition of 0.3 wt% MWCNTs. Significant improvement in hardness up to 1470 HV2 in the NbC-M2 HSS-0.3 wt% MWCNTs. MWCNTs bridges were detected as an effective toughening mechanism. No major compositional changes occurred by addition of MWCNTs.